Effect of Gravity on Repose Angle and Contact Forces of Particulate Pile Composed of Non-monodispersed Particles - H. Chen; Y. X. Chen; Q. S. Wei; Y. S. Shi (International Journal of Aerospace Engineering)
Evaluating the repose angle of granular materials under different kinds of gravitational conditions is essential for in situ resource exploration on surfaces of other Earth-like planets in the next decades. The forming process of particulate pile under different kinds of gravitational accelerations was simulated by three-dimensional discrete element method (DEM), where the particulate piles composed of normally distributed particles and lognormally distributed particles were considered, respectively. The effects of gravity on the repose angle and contact forces of the particulate pile were investigated. The results show that, for particulate pile composed of normally or lognormally distributed particles, the effect of gravity force on the repose angle is ignorable. For particles with a certain kind of size distribution, the distribution functions of normalized contact forces in the particulate pile under different gravity accelerations show to be in mutual coincidence. No obvious effect of the particle size distribution on the relation between the gravity acceleration and repose angle is observed.